TOR-inhibitor insensitive-1 (TRIN1) regulates cotyledons greening in Arabidopsis - Li, Linxuan; Song, Yun; Wang, Kai; Dong, Pan; Zhang, Xueyan; Li, Fuguang; Li, Zhengguo; Ren, Maozhi (Frontiers in Plant Science, 2015)
Target of Rapamycin (TOR) is an eukaryotic protein kinase and evolutionally conserved from the last eukaryotic common ancestor (LECA) to humans. The growing evidences have shown that TOR signaling acts as a central controller of cell growth and development. The downstream effectors of TOR have been well-identified in yeast and animals by using the immunosuppression agent rapamycin. However, less is known about TOR in plants. This is largely due to the fact that plants are insensitive to rapamycin. In this study, AZD8055 (AZD), the novel ATP-competitive inhibitor of TOR, was employed to decipher the downstream effectors of TOR in Arabidopsis. One AZD insensitive mutant, TOR-inhibitor insensitive-1 (trin1), was screened from 10,000 EMS-induced mutation seeds. The cotyledons of trin1 can turn green when its seeds were germinated on ½ MS medium supplemented with 2 µM AZD, whereas the cotyledons greening of wild-type (WT) can be completely blocked at this concentration. In addition, trin1 also showed a longer hypocotyl than that observed in WT in the presence of 2 µM AZD. Through genetic mapping, TRIN1 was mapped onto the long arm of chromosome 2, between markers SGCSNP26 and MI277. Positional cloning revealed that TRIN1 was an allele of ABI4, which encoded an ABA-regulated AP2 domain transcription factor. Plants containing P35S::TRIN1 or P35S::TRIN1-GUS were hypersensitive to AZD treatment and displayed the opposite phenotype observed in trin1. Importantly, GUS signaling was significantly enhanced in P35S::TRIN1-GUS transgenic plants in response to AZD treatment, indicating that suppression of TOR resulted in the accumulation of TRIN1. These observations revealed that TOR controlled seed-to-seedling transition by negatively regulating the stability of TRIN1 in Arabidopsis. For the first time, TRIN1, the downstream effector of TOR signaling, was identified through a chemical genetics approach.